Densification of Al powder and Al–Cu matrix composite (reinforced with 15% Saffil short fibres) during axial cold compaction - Moreno Gomez, Mario Fredy (2011)
Pure Al, Alumix 13 (Al–4.5 wt.% Cu 0.5 Mg 0.2 Si) powders and Alumix13 reinforced with 15 wt.% Saffil short fibers were compacted up to 250–386 MPa in an axial die to study their compacting behavior. The final relative densities D were higher than 0.95 for all unreinforced powders and 0.86 for the composite. Different micromechanical and phenomenological models were used to fit density–pressure relations. Arzt model describes the powder compaction with good agreement up to D ~ 0.85. Kawakita equation results as a best linear fit for all tests, but its compressibility parameter b is not in agreement with the hardening behavior of the composite. Panelli and Ambrosio equation could describe the data fairly well qualitatively for all compactions tests, however, over a limited pressure range. Finally, Konopicky relationship turned out to be very useful and fitted the densification data of all three materials quite well. Its slope from linear P vs. ln (1/(1−D)) plots, is related to the yield stress and characterizes thework hardening developed during plastic deformation while the density was increased. Microhardness values increase with the compacting pressure and such tendency agrees with the rising values of yield stresses, obtained by Konopicky.